SCREENING OF RICE VARIETIES SUITABLE FOR DIRECT SEEDING IN PUNJAB - R. I. Ali; T. H. Awan; Z. Manzoor; M. M. Ashraf; M. E. Safdar; M. Ahmad (Journal of Animal and Plant Sciences, 2007)
Studies regarding suitable rice varieties for direct seeding were conducted in RCBD with three replications at Rice Research Institute, Kala Shah Kaku, Sheikhupura, Pakistan during 2003 and 2004. The experiment comprised 15 medium and fine grain rice varieties viz: KS-282, IR-6, NIAB-1R9, Super Basmati, Basmati-2000, Basmati-385, Basmati-198, 98801, 98316, 98410, 98506, 97502, PK-5261-1-2-1, 99417 and 99512. The varieties were sown on 23-06-2003 during 2003 and 11-06-2004 during 2004. The results revealed that short stature and low tillering, medium and fine grain varieties viz ; KS-282, NIAB- IR9, IR-6, Basmati-2000, Super Basmati, 99512 and PK-5261-1-2-1 produced significantly higher yield than all the other varieties/lines under test.
Keywords: Rice (Oryza sativa); Varieties / genotypes; direct seeding; yield